Empirical Analysis and Forecast of Electricity Demand in West African Economic and Monetary Zone: Evidence from Panel ADRL Modelling - Hervé, DRAMA Bedi Guy (Asian Journal of Economic Modelling, 2018)
The present research work aims at analyzing on one hand, the residential demand of electricity and on the other hand forecasting it. The research involves a four-country panel from the West African Economic and Monetary Union (WAEMU) over the 1991-2016 periods. The outcomes of the ADRL modelling according to the PMG estimation show an existing long term relationship among the housing demand of electricity, the energy price, and the populations’ income and its growth. Those results also show that the consumers’ electricity demand is inelastic compared to the price but it is elastic in comparison to their incomes. The long term elasticity superior to the short term one shows that consumers’ reactions to the change of price and revenue are observable through times. Concerning the forecasting of the residential electricity demand, the results of the evaluation from the RMSE criterion of the predictive capacity of the homogenous and heterogeneous estimators show that the homogenous estimators provide better forecasting for the residential electricity demand in the WAEMU areas.